IMPROVING STUDENTS COMPREHENSION IN READING DESCRIPTIVE TEXT USING STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE - julianti, Julianti; Regina, Regina; Salam, Urai (FKIP - Universitas Tanjungpura, 2020)
The purpose of this research is to find out how STAD technique did improve students comprehension in reading descriptive text. The action hypothesis in this research was stated that teaching reading descriptive text using Student Team Achievement Divisions (STAD) technique can improve the achievement of the eighth grade students of MTSN 2 Pontianak. Classroom action research was used in conducting this research in two cycles. The data were divided measurement test, observation checklist, and field note. The result of the implementation shows that after the researcher conducted the actions, the students reading comprehension improved as shown in the result of both the observation on the students activities during the actions and their individual quizzes mean scores. From the reading comprehension test, the mean score of the individual quiz 1 was 48.57 and the mean score of the individual quiz 2 was 75.75. Student Team Achievement Divisions technique can improve reading comprehension of main idea, details, reference and inference.